2022
DOI: 10.1186/s13256-022-03295-w
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome in adults: a case report and review of the literature

Abstract: Background The current coronavirus disease pandemic has brought recognition of multisystem inflammatory syndrome in adults as a de novo entity, temporally associated with severe acute respiratory syndrome coronavirus 2 viral infection in adults. Hypothesis about its true pathophysiology remains controversial. Case report The patient was a 22-year-old African American female presenting to the emergency department with fever, sore throat, and neck sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…After reviewing the literature, a large variety of management strategies and therapeutic approaches are suggested 12 . In the current study, the patient received broad‐spectrum antibiotics, steroids, vasopressors, immunomodulators (anakinra), and IVIG treatment in addition to fluid resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the literature, a large variety of management strategies and therapeutic approaches are suggested 12 . In the current study, the patient received broad‐spectrum antibiotics, steroids, vasopressors, immunomodulators (anakinra), and IVIG treatment in addition to fluid resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…At least four of the following criteria should exist: polymorphous rash excluding bullous or vesicular eruptions, conjunctival injection, oropharyngeal mucous membrane changes, extremity changes, and lymphadenopathy. Symptoms common to MIS‐C but not typical of classic Kawasaki disease include abdominal pain, which is often more severe than in classic Kawasaki disease; thrombocytopenia, anemia, and lymphopenia; and elevated levels of ferritin, troponin, and D‐dimer, 12 Septic shock: symptoms include fever, tachypnea, tachycardia, hypotension, and signs of tissue hypoperfusion. Its diagnosis is based on the recovery of the pathogen by culture. Scarlet fever: rash, fever, and lymphadenopathy are present.…”
Section: Case Reportmentioning
confidence: 99%
“…Seventy different systemic organ-specific disorders were identified to be associated with post-COVID-19 symptoms [ 51 ]. The mechanisms involved are not fully understood; however, most clinicians and researchers agree that inflammation is the number one reason for these long-term sequelae followed by the induction of hypoxia [ 52 , 53 , 54 , 55 ]. Both inflammation and hypoxia are the results of metabolic reprogramming (MR) caused by the virus and persist in patients, especially those with underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular and cellular mechanisms leading to chronic inflammation remain unclear, and the cellular factor(s) implicated in the persistence of inflammation are also unknown. We hypothesize that SARS-CoV-2 mimics other viruses in reprogramming the metabolism resulting in chronic inflammation [ 55 ]. Several labs described that SARS-CoV-2 reprograms the metabolism to aid in viral replication [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case series byMagro et al. in the year 2020 discusses the pathology of MIS-A with features of endotheliitis and deposition of complement in the vessels[8].According to Behzadi et al, in an article published in 2022, out of 36 reported MIS-A cases documented, 17 cases had COVID-19 infection confirmed via RT-PCR, antibody tests, and clinically[9]. In the case series published on October 2020 by Morris et al, it was found that a significant number of cases (8/27) of MIS-A had negative Polymerase Chain Reaction (PCR) and positive SARS CoV-2 antibody test results, thereby suggesting that MIS-A might represent a post-infectious process[7].…”
mentioning
confidence: 99%